Endoscopic Findings In Patients Undergoing Upper Gastrointestinal Endoscopy For Various Indications: A Retrospective Study - Khanal, Ajit; Shrestha, Swarup; Shrestha, Ananta; Lama, Thupten; Kansakar, Romeo Bir Singh (Journal of Society of Surgeons of Nepal, 2024)
Introduction: Upper gastrointestinal (UGI) endoscopy is a safe procedure performed for analysis of indications and findings in patient presenting with various gastrointestinal symptoms including dyspepsia. This study aimed to evaluate the findings of UGI endoscopy in a tertiary care level hospital in Kathmandu. Methods: A retrospective cross-sectional observational study of consecutive patients who had undergone UGI endoscopy at Department of Gastroenterology, Alka Hospital over a period of nine years (2016-2024) was conducted. Data was extracted from the records of the patients including demographic, clinical presentation, indications and findings and was analysed using SPSS version 30. Results: Eight thousand five hundred and fifty-two patients who underwent UGI endoscopy for dyspepsia and various other indications were included for the study, 4339 (50.7%) males, 4213 (49.3%) females, age range of 2-103years (mean age ± SD = 45.80 ± 15.38). The most common finding seen were gastritis 4298(50.3%), gastro-duodenitis 560 (6.5%), gastric ulcer 429 (5%), duodenal ulcer 276 (3.2%), duodenitis 277 (3.23%), oesophagitis 170 (2%), hiatus hernia 194 (2.22%), gastric polyp 153 (1.8%), oesophageal varices 100 (1.2%), gastrointestinal malignancy (0.78%) and no lesions; that is normal findings in 1687 (19.7%). Conclusion: UGI endoscopy is a relatively safe procedure and is performed for various indications including the commonest presentation of dyspepsia. Gastritis was the most common finding followed by Gastroduodenitis, Gastric and duodenal ulcers, Duodenitis, Hiatus Hernia, esophagitis, Polyps, Esophageal varices and Malignancy, while one-fifth of those undergoing the procedure had functional dyspepsia with normal findings.